Efecto de la mecanización y fertilización en la serie de suelos Pichilingue sobre el comportamiento agronómico de plantas de maíz híbrido INIAP H-554 - Cobeña Arguello, Colling Anderson (2021)
The management of both edaphic and foliar fertilization, as well as its application according to the changes generated by the mechanization of the soil are determining factors of corn production. Considering the above, the present research aimed to evaluate the effect of the mechanization and fertilization of corn on the physical properties of the soil and yield. The test was carried out in the Soil Department of the National Institute for Agricultural Research (INIAP), located at km. 5.5 of the Quevedo - El Empalme road. Three factors were studied: Factor A: Edaphic fertilization (A1: Without edaphic fertilization, A2: N-P-K and A3: Complete fertilization); Factor B: Tillage (B1: Without tillage and B2: With tillage) and Factor C: Foliar fertilization (C1: Without foliar fertilization and C2: With foliar fertilization). The results obtained allowed to identify that the agronomic behavior of the crop varied in each treatment for the variables stem diameter and plant height, however, the weight of 100 seeds and ears that were longer were presented in T6: NPK + SL + CFF, (51.15 g and 17.05 cm) and the diameter of the ears was greater in T8: NPK + CL + CFF (4.79 cm). The combination of complete fertilization in the absence of tillage and in the absence of foliar fertilization allowed obtaining a higher level of yield in the maize hybrid under study (3597.86 kg ha-1). The economic benefit was greater when combining complete fertilization with the absence of tillage and the absence of foliar fertilization, with a 64.05% profitability. Keywords: lodging, complete fertilization, soil tillage, yield.